Thoracic Extramedullary Hematopoiesis Mimicking Metastatic Cancer. Issue 4 (October 2016) - Ha, Duc; Liao, Xiaoyan; Wang, Huan-You; Jamieson, Catriona; Magaña, Marisa; Makani, Samir
Abstract : Thoracic extramedullary hematopoiesis (EMH) is a rare manifestation in patients with myeloproliferative neoplasm. A 76-year-old woman with a long-standing history of polycythemia vera presented with a 2-month history of worsening dyspnea and left-sided wheezing. A chest computed tomography showed an ill-defined soft tissue mass encasing the left mainstem bronchus causing airway obstruction, associated with paratracheal and paraesophageal lymphadenopathy. Endobronchial ultrasound-guided fine needle aspiration of the soft tissue mass and mediastinoscopy with excisional biopsy of a paratracheal lymph node demonstrated EMH with increased myeloid blasts. A bone marrow biopsy confirmed postpolycythemic myelofibrosis consistent with progression of polycythemia vera to myelofibrosis. We describe the bronchoscopic management of a case of EMH presenting as a mediastinal mass, mimicking malignancy.